## Algebra and Trigonometry 10th Edition

Published by Cengage Learning

# Chapter 4 - 4.4 - Translations of Conics - 4.4 Exercises - Page 348: 56

#### Answer

$\dfrac{x^2}{48}+\dfrac{(y-4)^2}{64}=1$

#### Work Step by Step

The standard form of the equation of an ellipse when the major axis is horizontal can be expressed as: $\dfrac{(x-h)^2}{a^2}+\dfrac{(y-k)^2}{b^2}=1$ Where $(h,k)$ is the center, $2a$ is the major axis length, and $2b$ is the minor axis length. The standard form of the equation of the ellipse when the major axis is vertical can be expressed as: $\dfrac{(x-h)^2}{b^2}+\dfrac{(y-k)^2}{a^2}=1$ Where $(h,k)$ is the center, $2a$ is the major axis length, and $2b$ is the minor axis length. The center is the midpoint of the foci: $(\dfrac{0+0}{2}, \dfrac{0+8}{2})=( 0, 4)$ The ellipse is in the horizontal axis, so the distance between the vertices is equal to $2a$: $b=\sqrt{a^2-c^2}=\sqrt {8^2-4^2}=\sqrt {48}$ $\dfrac{(x-0)^2}{(\sqrt {48})^2}+\dfrac{(y- 4)^2}{(8)^2}=1$ or, $\dfrac{x^2}{48}+\dfrac{(y-4)^2}{64}=1$

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.